'You can't pick up a phone and talk to someone': How algorithms function as biopower in the gig economy. (January 2021) - Walker, Michael; Fleming, Peter; Berti, Marco
This paper asks why there is so little collective dissent and mobilised resistance in the gig economy, especially when labour-based digital platforms are used. We suggest part of the answer lies with 'management by algorithm'. Drawing on an empirical study of Uber drivers in Australia, we found that algorithms function as a form of biopower, a concept introduced by Michel Foucault. As Uber drivers 'life processes' are put to work, fragmentation, isolation and resignation ensue. We explore the implications that our findings have for appreciating how biopower operates within platform capitalism and beyond.